x⁵ + 2x⁴ - x - 2 = (x⁵ + 2x⁴) - (x + 2) = x⁴(x + 2) - (x + 2) = (x + 2)(x⁴ - 1) =
= (x + 2)(x² - 1)(x² + 1) = (x + 2)(x - 1)(x + 1)(x² + 1)
у первых двух множителей возьмем х⁴
тогда получим: х⁴ * ( х + 2 ) - ( х + 2)
теперь выносим ( х + 2 ):
( х + 2 ) * ( х⁴ - 1 )
x⁵ + 2x⁴ - x - 2 = (x⁵ + 2x⁴) - (x + 2) = x⁴(x + 2) - (x + 2) = (x + 2)(x⁴ - 1) =
= (x + 2)(x² - 1)(x² + 1) = (x + 2)(x - 1)(x + 1)(x² + 1)
у первых двух множителей возьмем х⁴
тогда получим: х⁴ * ( х + 2 ) - ( х + 2)
теперь выносим ( х + 2 ):
( х + 2 ) * ( х⁴ - 1 )